Diffusion multiple study of the Co-Fe-Ni system at 800 °C. (March 2019) - Yuan, Yuan; Chen, Tao; Li, Dajian; Gerhards, Uta; Pan, Fusheng; Seifert, Hans; Moelans, Nele
Abstract: The Co-Fe-Ni system is a key system in a wide range of industrial applications. Knowledge of the thermodynamic and kinetic properties of the system is crucial for the alloy and process design. Although the system has been studied extensively, there remain several unexplained discrepancies between different literature data and, for mediate low temperatures, the information is scarce. In this work, a high throughput diffusion multiple approach was applied. The isothermal phase diagram section at 800 °C was determined using the Co-Fe-Ni multiple. The interdiffusion coefficients of the binary Co-Fe, Co-Ni, Fe-Ni systems and their composition dependence were calculated using the Sauer-Freise method based on the compositional profiles obtained from the diffusion multiple. Different from previous experimental results for mediate low temperature, our results coincide with the extrapolated Arrhenius temperature dependence from diffusion coefficient data at high temperature range. These observations are important for a better understanding and modelling of the interdiffusion behavior in this key alloy system. Highlights: Diffusion multiple of Co-Fe-Ni system is assembled and annealed at 800 °C. Isothermal section at 800 °C of Co-Fe-Ni is determined. Interdiffusion coefficients ( D ̃ ) of Co-Fe, Co-Ni and Ni-Fe systems is obtained. Obtained D ̃ values are coincident with literature data at high temperatures.